Socio-Psychological Characteristics of The Formation of Ecological Consciousness in A Person (Eurasian Journal of Learning and Academic Teaching, 2024)
The main reason for this is the mutual convergence of the relationship between man and nature, as well as the mutual integration of the "society-man-technology-natural environment" system. Also, in the current global environment, studying the relationship between man and nature, protecting the ecological environment, forming environmental consciousness and culture in people, and reducing the impact of the human factor on nature are becoming urgent tasks for many sciences.